Integrasi Neurosains Dalam Pendidikan: Studi Literatur Tentang Proses Belajar Berbasis Otak: The Integration of Neuroscience in Education: A Literature Review on Brain-Based Learning Processes - Siti Nurfadlah Fadlah; Ahmad Muttaqin; Iis Maesaroh (Paidagogia: Jurnal Pengajaran dan Pendidikan, 2024)
This study aims to examine the integration of neuroscience in education through a literature review on brain-based learning processes. Neuroscience provides deep insights into how the brain processes, stores, and retrieves information, which can be used to design more effective learning strategies that align with how the brain functions. In this study, various literature related to neuroscience and education were analyzed to identify key principles underlying the learning process, such as attention, memory, and motivation. The findings indicate that understanding the structure and function of the brain, including the role of the prefrontal cortex, amygdala, and hippocampus, is crucial for developing more adaptive and effective teaching methods. Integrating neuroscience into education can help create a more conducive learning environment, optimize student engagement, and improve learning outcomes. Therefore, collaboration between educators and neuroscientists is key to implementing a brain-based educational approach.